Analysis of the Impact of Technological Innovation and Design Creativity on the Attractiveness of Tourism Destinations in Bali (West Science Interdisciplinary Studies, 2024)
This research investigates the impact of technological innovation and design creativity on the attractiveness of tourism destinations in Bali. A quantitative approach was employed, collecting data from 267 tourists visiting various destinations in Bali. Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis was used to analyze the relationships between technological innovation, design creativity, and destination attractiveness. The results revealed significant positive relationships between technological innovation and destination attractiveness (β = 0.543, p < 0.001) and between design creativity and destination attractiveness (β = 0.486, p < 0.001). The model fit assessment indicated satisfactory fit indices for the SEM-PLS model. Overall, the findings highlight the importance of leveraging technological innovation and design creativity to enhance the attractiveness of tourism destinations in Bali and foster sustainable tourism growth.